COMPARISON OF TOPSIS AND VIKTOR METHODS IN SCHOLARSHIP SELECTION OF AISYAH UNIVERSITY - Alfina Alfina; Fahlul Rizki; Ulfa Isni kurnia; Ockhy Jey Fhiter Wassalam (Sean Institute, 2022)
Higher education institutions, especially private-level universities, offer many scholarships to prospective students. Scholarships are sourced from universities, and the requirements for obtaining scholarships for prospective students will be selected and meet the specified requirements, for example, the hafiz/hafidzah must meet one of the requirements of having a certificate or certificate of hafiz/hafidzah . The scholarship program aims to realize the expectations of the underprivileged and have good academic potential in pursuing higher education.This study examines the comparison of TOPSIS and VIKTOR methods in the selection of scholarships at Aisyah University. The TOPSIS method has a simple and easy-to-understand concept, besides that the TOPSIS method can measure the relative performance of decision alternatives in a simple mathematical form. The Vise Kriterijumska Optimizacija I Kompromisno Resenje (Vikor) method makes multi-criteria decisions or what is often known as Multi-Criteria Decision Making (MCDM). MCDM is used to solve problems based on conflicting and disproportionate criteria. The TOPSIS method has the highest accuracy rate of 80% in 12 trials, while the VIKOR method only has the highest accuracy rate of 60%. Based on these results, it can be concluded that the TOPSIS method can be used to select outstanding student scholarships for the underprivileged at Aisyah University